Evaluation of Guantánamo Medical Sciences students during the active research before COVID-19 - Leonardo Antonio Salgado Delgado (Universidad de Ciencias Médicas de Granma, 2022)
Introduction: at present, the world is facing the SARS-CoV-2 infection, in Cuba students contribute with epidemiological surveys, support in isolation centers, perform active community research. Objective: to characterize the behavior of students of Medical Sciences during the active search for COVID-19 in the medical office # 9 Paraíso of Baracoa municipality. Methods: a cross-sectional descriptive observational study was carried out from March to June 2021, the universe and coincident sample consisted of 18 students who met the inclusion criteria with prior informed consent; the variables under study were: biological sex, knowledge about Covid-19, symptoms and preventive measures, hygienic-sanitary behaviors, sources of information about COVID-19 and emotional sphere. Results: female sex predominated, 100 % of the students received training in educational centers and advice from health personnel, who have correct knowledge about symptoms and preventive measures; in the emotions before the research work, 61.1 % referred fear of contracting the disease; in the hygienic-sanitary behavior, the use of the mask and the physical distance between students and with the population represented 100 % and only 11.1 % performed the correct hand hygiene. Conclusions: in the final evaluation of the students, adequate behaviors predominated and inadequate behaviors were not recorded.